Międzynarodowa kontrola nierozprzestrzeniania broni jądrowej - Gadkowski, Tadeusz (Wydział Prawa i Administracji UAM, 1983)
The article discusses issues of international law related to the implementation of provisions of the Non-Proliferation Treaty. The author's study on the control activities of the International Atomic Energy Agency in the field of non-proliferation of nuclear weapons constitute the basic part of the article. In the light of provisions of the Treaty the MAEA is the sole competent organ to perform international control of its observance. Subjective and objective scope of the MAEA control activities in this range is defined in the Treaty provisions and the specific control procedures —- in the provisions of the Agency Statute and in its specific regulations (Safeguards Document, Inspectors Document) as well as in the provisions of Safeguards Agreements. Essentially, the author focuses on problems of Safeguards Agreements concluded in a result of implementation of the Treaty provisions. Safeguards Agreements concluded by the Agency and a State of a group of member States, contain regulations on general grounds and rules of control activity of the Agency in the scope of peace nuclear activities of member States and provisions defining procedure of applying control mechanisms. The author discusses substantiate of these agreements on the example of a typical agreement of MAEA with Poland, and interprets its basic provisions. A considerable part of the article is the assessment of effectiveness of the control system of International Atomic Energy Agency in the light of implementation of provisions of the Non-Pirolif eration Treaty.
International controls on non-proliferation of nuclear weapons